Analisis Potensi Likuefaksi pada Lapisan Pasir dengan Metode Standard Penetration Test (SPT) - Rafly Hendriyansyah; Andikanoza Pradiptiya; Putera Agung Maha Agung; Muhammad Fathur Rouf Hasan (Teknik Sipil, Politeknik Negeri Ketapangg, 2026)
Liquefaction is one of the dangerous geotechnical phenomena that often occurs due to earthquakes, especially in saturated sandy soils that are not cohesive. Although the area of Langsa City, Aceh is classified as having relatively low seismic activity, the condition of the water-saturated soil still makes it vulnerable to this phenomenon. This study aims to analyze the potential for liquefaction at the Langsa Depot Project site using the Standard Penetration Test (SPT) method. The method used involves correcting the value of N-SPT to N1(60), then the calculation of the Cyclic Stress Ratio (CSR), Cyclic Resistance Ratio (CRR), and Safety Factor (FS) based on the. SPT data was obtained from one drill point with a depth of 50.5 meters and combined with regional seismic data (magnitude 5.1 SR and earthquake acceleration of 0.2 g). The results of the study showed three layers of silty sand that were the focus of the analysis, namely at depths of 6–8 m, 28–35 m, and 48–49 m. The first layer has an FS value of > 1 (1.083 – 1.168) which indicates that this layer does not have the potential for liquefaction, for the second layer has an FS value of > 1 (1.817 – 1.899), so it is declared not to have the potential for liquefaction and is categorized as safe, and the third layer has an FS value of > 1 which is (2.012) is also declared safe from potential liquefaction. These findings confirm the importance of liquefaction evaluation for safe geotechnical design. The study concluded that the project site has two zones that are vulnerable to liquefaction and require mitigation. Keywords: liquefaction, SPT, safety factor, sandy soil